Effects of different exercise intensity on bone mineral density in adults: a comparative systematic review and meta-analysis - Kast, Stephanie; Shojaa, Mahdieh; Kohl, M.; von Stengel, S.; Gosch, Markus; Jakob, Franz; Kerschan-Schindl, Katharina; Kladny, Bernd; Klöckner, N.; Lange, U.; Middeldorf, S.; Peters, S.; et al. (Osteoporosis international, 2022)
Purpose: The primary objective of the present systematic review and meta-analysis was to determine the effect of differing exercise intensity on (areal) bone mineral density (BMD) at lumbar spine and hip in adults by a comparative meta-analysis. Methods: A systematic review of the literature according to the PRISMA statement included: (a) exercise trials, (b) with ≥two study arms that compared different exercise intensities, (c) intervention ≥6 months, (d) BMD assessments at lumbar spine (LS) or hip. Five electronic databases were scanned without language restrictions up to July 2021. The present analysis of exercise intensity was conducted as a mixed-effect meta-analysis and applied “type of exercise” and “study duration” as moderator in subgroup analyses. Outcome measures were standardized mean differences (SMD) for BMD changes at the LS, and hip. Results: Eleven exercise studies with 26 study arms were included. Although the effect of high-intensity exercise was more pronounced on LS-BMD (SMD: 0.19, 95%-CI: 0.61 to -0.23) and hip-ROI (0.17, 0.38 to -0.04), we did not observe significant differences between the groups (LS-BMD: p=0.373 and hip-BMD: p=0.109). We observed a substantial level of heterogeneity between the trials for LS- but not for hip-BMD. Applying “type of exercise” and “study duration” as moderators did not significantly modify the differences between low and high exercise intensity on BMD at LS or hip. Conclusion: There is insufficient evidence for a superior effect of high-intensity exercise on areal BMD at lumbar spine and hip in people aged 50 years and older. Varying exercise intensity with periods of lower exercise intensity intermitted by higher intensity might be a promising option to address the issue of exercise intensities in intervention studies.
CRIS-Team Scopus Importer:2022-03-25
Keywords: BMD; Exercise; Intensity; Meta-analysis; Type of exercise